Knowledge and practice of menstrual hygiene among adolescent girls in Kathmandu valley. - Pandey, Ashok (2011)
SUMMARY: Menstruation is the monthly uterine bleeding through the vagina for around four to five days every twenty eight days during the reproductive life of a female, from menarche to menopause. The Descriptive, cross-sectional studies were carried out to explore the knowledge and practices of menstrual hygiene. The collected data were systematically and thoroughly analyzed and interpreted under the basis of stated objectives, research questions FGD guidelines and the findings. The findings are as follows: The findings of the study revealed that majority of students 59% were of the age below 14-15 years. Majority of the respondents 93% were unmarried, Hindus 67% and 26% from Brahmin ethnicity. Regarding menarche, the respondents who responded lowest age of onset of menarche was at the age of 11 and highest at the age of 15. The mean age of onset was 12.37% years. Nine out of ten adolescent girls were going to school during period and 41% of girls told that they don't cook food during the menstrual period. More than half 55% of the respondents were told that ageing is the cause of Menstruation Followed by hormone 42%. Regarding the information on menstruation, 84% of the adolescent girls told that menstruation is the Physiological process. 16% as a Pathological process 43% were agreed on the teaching of parents and 39% were agreed on teaching of all of above (Course book, Teacher, Parents). Fifty percent of the adolescent girls were changed the pad daily Where, 83 percent were used special pads and remaining 17 percent were used the old clothes in menstrual period. Majorities 94% were not shared and 6 percent only shared the pad and 88% were re used and 12% were not re used. Maximum percent 50% were disposed in dustbin followed by 43 percent in separate place and 7 percent in mud. Most of the girls expressed that 71 percent feel upset and tension during the first time of menstruation. And, remaining 29 percent feel normal during menstruation for the first time. First menstruation is often traumatic and very negative experience. More than half fifty five percent of the respondents were told that ageing is the cause of Menstruation. Eighty four percent of the adolescent girls told that menstruation is the Physiological process and sixteen percent as a Pathological process. Six percent of the adolescent girls shared the pad and eighty eight percent were re used. Most of the girls expressed that seventy one percent feel upset and tension during the first time of menstruation.